2012
DOI: 10.2166/wh.2012.183
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of pathogen concentrations in a drinking water source using hydrodynamic modelling and microbial source tracking

Abstract: The faecal contamination of drinking water sources can lead to waterborne disease outbreaks. To estimate a potential risk for waterborne infections caused by faecal contamination of drinking water sources, knowledge of the pathogen concentrations in raw water is required. We suggest a novel approach to estimate pathogen concentrations in a drinking water source by using microbial source tracking data and fate and transport modelling. First, the pathogen (norovirus, Cryptosporidium, Escherichia coli O157/H7) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Nguyen et al (2016) also reported in their modelling study that diffuse sources had substantial contributions to the total coliform concentrations in the Vietnamese Red River, but that was unlikely to increase near future (2050s) concentrations significantly. Comparatively lower diffuse source contributions are also reported in other studies (Ouattara et al, 2013, Sokolova et al, 2012, Gao et al, 2015.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Nguyen et al (2016) also reported in their modelling study that diffuse sources had substantial contributions to the total coliform concentrations in the Vietnamese Red River, but that was unlikely to increase near future (2050s) concentrations significantly. Comparatively lower diffuse source contributions are also reported in other studies (Ouattara et al, 2013, Sokolova et al, 2012, Gao et al, 2015.…”
Section: Discussionsupporting
confidence: 72%
“…While diffuse sources (urban and agricultural runoff) contributed less, up to 9.3% for E. coli and 12.6% for enterococci. Comparatively lower contribution from diffuse sources was also reported in other studies (Ouattara et al, 2013, Sokolova et al, 2012, Gao et al, 2015. During the wet period, a higher contribution from the upstream boundary is expected, because the river here is connected to the Bhairab River in the north and carries contaminated runoffs from the upstream urban and agricultural areas.…”
Section: Impact Of Different Processes On Fib Concentrationssupporting
confidence: 65%
See 1 more Smart Citation
“…In Sweden, coupling fate and transport modeling with QMRA is still relatively rare, but some examples exist [23] and simplified methods have been developed for practical application to meet the increasing interest and need, see e.g., Åström and Johansson [24], Åström, Lindhe, Bergvall, Rosén, and Lång [17]. Additionally, an approach combining incidence data with hydrodynamic modeling to estimate pathogen concentrations for QMRA and the effect of mitigation measures has been suggested [25,26]. Measurements of FIB and pathogen concentrations would enhance the applicability of the fate and transport modeling and add to the overall risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of another study (Sokolova et al 2012b), the 105 contribution from the cattle grazing area to the concentrations of Bacteroidales genetic markers at 106 the water intake was approximately 1 log 10 unit less compared to the contributions from the on-site 107 systems and from the Pixbo Päls pumping station. Furthermore, in a study on the pathogen 108 concentrations in this lake (Sokolova et al 2012a), it was found that the contributions from the cattle 109 grazing area and the urban area to the Cryptosporidium concentrations at the water intake were 110 approximately 1 and 3 log 10 units less than from the Pixbo Päls pumping station, respectively. In 111 summary, based on the results of the earlier studies of this lake, we have concluded that the 112 contribution from these nonpoint sources is generally much smaller than from the other identified 113 contamination sources.…”
mentioning
confidence: 96%